ANALISIS KOMPARATIVE PENGARUH CASH RASIO DAN DEBT TO ASSETS RASIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN OTOMOTIF DAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jhon Nasyaroeka (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
In this research between variable cash rasio and debt to assets rasio as independent variableas well as thr return on assets as the dependent variable on both good company that the companyautomotive and Telecommunication company has influence with the same or simultaneously,throughthe test F.And this reseach no difference in the influence of simultaneously of independent variablewith the dependent variable